DESIGN AND CHARACTERIZATION OF MICROEMULSION GEL FOR TRANSDERMAL DRUG DELIVERY SYSTEM OF DULOXETINE HYDROCHLORIDE - Tole, Karishma; Deshmukh, Ganesh (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective was to improve the bioavailability, stability of formulation, and skin permeability of Duloxetine HCl. Method: Microemulsion was prepared with oleic acid as oil, water, and Smix ratio of tween 20 to propylene glycol (1:3). Pseudo-ternary phase diagrams were constructed to determine the region of existence of microemulsions prepared using oil titration method. Optimization of formulations was done based on the in vitro diffusion studies. The microemulsion was gelled using carbopol 934p and HPMCK 100 as the gelling agent. Result: After the analysis of different evaluation parameter and drug release, the F3 batch was selected as a promising formulation for delivery of duloxetine HCl as a microemulsion gel for transdermal drug delivery with 79.607% drug release in 10 h. Conclusion: It was observed that transdermal microemulsion gel can be formulated successfully for duloxetine HCl with improved bioavailability. Among the other batches, the F3 batch was selected as an optimized batch because all the evaluation parameters results are satisfactory. From stability data, the formulation was found to be stable as no phase separation or turbidity was observed in the formulation after 3 months.